The Influence of Celebrity Endorsement, Price, and Electronic Word of Mouth on Purchase Intention with Brand Image as a Mediator in Skincare Products in Banda Aceh City (International Journal of Scientific Research and Management (IJSRM), 2025)
This study examines how celebrity endorsements, price, and electronic word-of-mouth (eWOM) influence consumers’ purchase intention for skincare products, with brand image serving as a mediating variable. The fieldwork was conducted in Banda Aceh City, involving 190 respondents selected through purposive sampling. A quantitative research design was employed, and data were analyzed using SmartPLS software. The findings indicate that celebrity endorsement has a significant positive effect on brand image (p = 0.000) and directly enhances purchase intention (p = 0.001). Brand image itself significantly increases purchase intention (p = 0.003), confirming its mediating role between external variables and consumers’ final purchasing decisions. While eWOM demonstrates a weak association with brand image (p = 0.067), it shows a strong and positive direct effect on purchase intention (p = 0.000). In contrast, price has no significant effect on brand image (p = 0.954) but exhibits a significant direct influence on purchase intention (p = 0.000). In summary, consumers in Banda Aceh are primarily influenced to purchase skincare products by celebrity endorsements, eWOM, and price, with brand image acting as a cognitive channel through which these external factors shape purchasing behavior..